An open label, single arm, pilot study to evaluate the safety, tolerability, and efficacy of daily fluconazole 150 mg in subjects suffering from Tinea cruris and Tinea corporis [version 1; peer review: awaiting peer review] - Saple, Dattatray Gopal; Save, Sushrut; Kumar, Devesh; Sood, Suneet (F1000 research, 2022)
Background: Dermatophytes are the most common superficial fungal infections worldwide and are treated with prescribed regimens of terbinafine and itraconazole, or with weekly doses of fluconazole. Dermatologists are increasingly encountering treatment failures, and experts suggest that standard treatment regimens are not applicable anymore. We planned an open-label study to evaluate the results of fluconazole 150 mg daily for 8 weeks in patients with tinea cruris and tinea corporis. Methods: Patients were enrolled from the La'Mer Clinic, Mumbai, India. We included adult subjects with uncomplicated dermatophytosis confirmed by microscopic examination of skin scrapings. Pregnancy, poor renal function, and recent exposure to anti-fungal therapy were exclusion criteria. Patients were reviewed on days 14, 28 and 56. The treating doctor scored the severity of erythema, scaling, and pruritus on a four-point scale: absent, mild, moderate, and severe. Of 107 subjects screened, 100 were finally included in the study. Eleven were lost to follow up and one subject withdrew consent. Results: The site of disease was body alone in 29, groin alone in 7, and both body and groin in 64 cases. At 5 weeks, 98%, 100%, and 97% of patients had no scaling, erythema, and pruritus, respectively. Skin scrapings showed 100% mycological cure. In one patient the alanine transaminase level rose from 54.9 to 100.2 U/L, and qualified as a grade 1 adverse event not requiring intervention. No other significant adverse events were noted. Conclusions: Our results suggest that fluconazole 150 mg daily for eight weeks effectively treats dermatophytosis. This regimen is safe and well-tolerated even in patients with co-morbidities. Fluconazole is about eight times less expensive than itraconazole or terbinafine and may be the preferred therapy. Registration: The trial was registered with Clinical Trials Registry, India (Registration number CTRI/2020/06/026110) on 24 June 2020. FDC Company, India, provided financial support for the study.